Knowledge Regarding COVID-19 among Registered Nurses of Pokhara, Nepal - Kafle, Akriti; Pahari, Sirjana Pandit; Khanal, Sudip; Baral, Kushalata; Pathak, Kabita; Baral, Suraj; Kafle, Anil; Dahal, Maginsh (Europasian Journal of Medical Sciences, 2020)
Background: Coronavirus disease is an emerging pandemic disease. The whole world is suffering from this disease these days. It is an acute respiratory disease in which transmission occurs essentially through respiratory droplets and this virus said to have 2-14 days of incubation. Objective: To assess their knowledge regarding COVID19 among registered nurses of Pokhara valley. Methods: A descriptive cross-sectional study was performed with the help of the pretested and self-administered questionnaires to 750 registered nurses of Pokhara valley. Thus collected data was entered into SPSS version 20 and then further analyzed using R software. Frequency, percentages, the mean and standard deviation were calculated for the analysis. p-value was calculated where ever applicable to find the significance of data. Results: The study disclosed that mass of the respondents had moderate proportion (44.8%) concerning understanding, followed by the respondents had a low level of knowledge (29.2%) and the rest of them (26.0%) had good knowledge about COVID 19. Conclusion: Overall knowledge among nurses was found to be satisfactory as the disease is entirely new. Further research and updates on the diseases will help to profound knowledge among nurses.